The Influence of Auditor Characteristics on Audit Report Lag: The Effectiveness of the Audit Committee as a Moderating Variable - Vionita, Laura; Kristianti Maharani, Novera (Journal Research of Social Science, Economics, and Management, 2025)
Audit report lag reflects the timeliness of audit completion and serves as a crucial indicator of transparency in financial reporting. This study aims to examine the effect of auditor characteristics, namely audit tenure, size of Public Accounting Firm (PAF), and auditor industry specialization on audit report lag, with the effectiveness of the audit committee as a moderating variable. The research object includes 69 infrastructure sector companies listed on the Indonesia Stock Exchange during the 2021-2024 period, with a total sample size of 172 observations. A quantitative approach was used with secondary data and moderated regression analysis. The results show that audit tenure and the size of the PAF have no significant effect on audit report lag, while auditor industry specialization has a significant negative effect. The effectiveness of audit committee does not to moderate the relationship between audit tenure and the size of the PAF on audit report lag, but it significantly strengthens the effect of auditor industry specialization on audit report lag. This study is expected to contribute to decision making regarding auditor appointments and enhancing internal oversight to improve the timeliness of financial reporting. Future researchers are encouraged to expand the research scope across sectors and include additional variables such as audit complexity or internal audit quality for more comprehensive results.